The influence of protective varnish on the integrity of orthodontic cements - Érika Machado Caldeira; Antonio de Moraes Izquierdo; Felipe Giacomet; Eduardo Franzotti Sant'Anna; Antônio Carlos de Oliveira Ruellas (Dental Press Editora, 2013)
OBJECTIVE: The aim of the present study was to assess the influence of saliva contamination over the structural strength and integrity of conventional glass-ionomer cements used for cementing orthodontic bands in the absence and presence of a surface-protecting varnish. METHOD: 48 samples were prepared by inserting 3 types of glass-ionomer cements into standardized metallic matrixes of 10 mm of diameter and 2 mm of depth. The cements used were: Meron (VOCO), Ketac-Cem (3M ESPE) and Vidrion C (DFL), all of which comprised groups A, B and C, respectively. Subgroups A1, B1 and C1 comprised samples with no surface protection, whereas subgroups A2, B2 and C2 comprised samples of which surface was coated with Cavitine varnish (SS White), after cement manipulation and application, in order to protect the cement applied. All samples were stored in artificial saliva for 24 hours at 37ºC. A Vickers diamond micro-durometer was used to produce indentations on the non-treated group (non-varnished) and the treated group (varnished). RESULTS: Varnished materials had significantly higher microhardness values in comparison to non-varnished materials. Ketac-Cem had the highest microhardness value among the varnished materials. CONCLUSION: Varnish application is necessary to preserve the cement and avoid enamel decalcification. Glass-ionomer cements should be protected in order to fully keep their properties, thus, contributing to dental health during orthodontic treatment.